Mediation of anxiety and coping strategies between severe discipline and interparental conflict with parenting stress - Docal-Millán María del Carmen; Riveros-Munévar Fernando; Acuña-Arango Lina María; Campos-García Ángela Ximena; Cabrera-García Victoria Eugenia (Heliyon)
Parenting stress is a complex process for parents who feel that the demands of their children upbringing overwhelm their roles. Parenting stress can be associated with anxiety, parental conflict and harsh discipline practices, and the use of coping strategies that positively buffer the effect of these variables on parents. Although the factors associated with parenting stress are well documented, the literature offers few models to explain the stress and the mediation of certain variables on Colombian families. The aim of this quantitative cross-sectional study was to analyze the mediation of anxiety and coping strategies in the relationship between 1) severe discipline and parenting stress, and 2) interparental conflict and parenting stress. A total of 1.373 fathers and mothers of Colombian children participated (Age M = 40.57; SD = 12.65). Questionnaires on parenting stress, severe discipline, perception of interparental conflict, anxiety and family functioning in crisis situations were applied. Severe discipline and interparental conflict accounted for 30 % of parenting stress. Anxiety mediated the relationship between severe discipline and parenting stress. Anxiety and cognitive restructuring mediated the relationship between interparental conflict and parenting stress. The findings show that parenting stress interventions are important in reducing severe discipline and interparental conflict by managing anxiety and using coping strategies such as cognitive restructuring. Thus, these measures contribute to the well-being of families, favoring the integral development of children.